Analisis Yuridis terhadap HAKI Sebagai Objek Perjanjian Fidusia dan Peran Notaris dalam Proses Pengikatan Jaminan - Maya Cahyani; Vanya Marchelya (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This study aims to provide a legal analysis of the position of Intellectual Property Rights (IPR) as an object of fiduciary security agreement, and the role and responsibility of notaries in the process of securing such collateral. The growth of the creative economy has led to the need for legal recognition of the economic value of intellectual property, allowing IPR to be treated as a viable asset for fiduciary guarantees. Under Indonesian positive law, IPR is recognized as intangible property that can be used as fiduciary collateral, particularly as regulated under Law No. 42 of 1999 on Fiduciary Guarantee and further supported by Government Regulation No. 24 of 2022 concerning the Creative Economy. In practice, the implementation of IPR as collateral remains challenging, especially regarding valuation, legal certainty of ownership, and the registration process. This is where the role of notaries becomes essential. A notary not only acts as a public official in drafting the fiduciary agreement deed, but also ensures the legality, validity, and legal protection of the rights and obligations of all involved parties. This research applies normative legal methods, using statutory and literature approaches to analyze current legal issues. The findings indicate that an active role of notaries is crucial to ensure the legality of fiduciary agreements involving IPR and to support broader access to financing based on intellectual assets. The study concludes that regulatory improvements and broader public understanding are necessary to strengthen the position of IPR as a reliable object of fiduciary security within Indonesia’s legal and economic framework.